ECOLOGICAL MONITORING: THE ROLE OF NEW TECHNOLOGIES IN THE CONSERVATION OF NATURAL RESOURCES - Garayev, Malik; Hashimov, Elshan (Collection of scientific papers «ΛΌГOΣ», 2025)
Ecological monitoring is a critical tool for the conservation of natural resources and sustainable environmental management. In recent years, factors such as environmental changes, climate change, population growth, and industrialization have made the conservation of ecosystems increasingly difficult. Issues such as radiation, air quality, water, and soil pollution require the application of modern technologies to monitor environmental conditions and identify risks in this field. The importance of ecological monitoring becomes evident here.